2014
DOI: 10.3233/npm-14814041
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of brain temperature using radiometric thermometry: Experimental validation and clinical observations in asphyxiated newborns

Abstract: BACKGROUND: Therapeutic hypothermia (HT) has been shown to decrease death and severe disability in infants with hypoxicischemic encephalopathy (HIE). Rectal temperature (RT) is used to determine the temperature set-points for treatment with HT, however experimental studies have shown significant differences between RT and brain temperature during HT. Knowledge of actual brain temperature during HT might allow better determination of optimal degree of cooling and improve outcomes. OBJECTIVES: To compare measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Injury patterns in this area are known to be associated with impaired temperature regulation (Bass et al . ). Several groups have shown that the degree of basal ganglia injury correlates with poor outcome (Martinez‐Biarge et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Injury patterns in this area are known to be associated with impaired temperature regulation (Bass et al . ). Several groups have shown that the degree of basal ganglia injury correlates with poor outcome (Martinez‐Biarge et al .…”
Section: Discussionmentioning
confidence: 97%
“…The device output temperature on day 3 of treatment most accurately correlated with MRI injury in the grey matter, including basal ganglia and thalamic injury. Injury patterns in this area are known to be associated with impaired temperature regulation (Bass et al 2014). Several groups have shown that the degree of basal ganglia injury correlates with poor outcome (Martinez-Biarge et al 2010;Massaro et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Radiometric thermometry A potential alternative to MRSI for measuring brain temperature is zero-heat-flux or radiometric thermometry through sensors placed on the forehead (37,38). Zeroheat-flux thermometry uses a temperature sensor and an electric heater to create an isothermal tunnel where the skin surface is heated to the temperature of the underlying tissue; the brain when the sensor is placed on the forehead (38,39).The potential benefits of zero-heat-flux thermometry are significant, as it may preclude the need for more invasive monitoring.…”
Section: Modalities For Non-invasive Brain Temperature Measurementmentioning
confidence: 99%
“…In a study by Bass et al (37), they used a radiometric thermometry sensor in 30 neonates with hypoxic-ischemic encephalopathy and found it effective in monitoring therapeutic hypothermia (37). The authors validated the radiometric thermometry sensors by using three mini-swine that were cooled to 33-34 • C using a cooling blanket.…”
Section: Modalities For Non-invasive Brain Temperature Measurementmentioning
confidence: 99%